Identifying and Classifying Quality of Life Tools for Assessing Neurogenic Bowel Dysfunction After Spinal Cord Injury. - Choukou, Mohamed-Amine; Best, Krista L.; Craven, B. Catharine; Hitzig, Sander L. (Topics in Spinal Cord Injury Rehabilitation)
Objectives: To identify and classify tools for assessing the influence of neurogenic bowel dysfunction (NBD) on quality of life (QoL) after spinal cord injury (SCI). Methods: In this systematic review, MEDLINE/PubMed, CINAHL, and Psyclnfo were searched to identify studies assessing the influence of NBD on QoL (or related construct) after SCI. Two independent reviewers screened titles and abstracts, and both reviewers classified tools as subjective or objective according to Dijkers' theoretical QoL framework. Results: Seventy-two studies were identified, and 35 studies met the inclusion criteria. Five objective measures assessed the influence of NBD on QoL, which were validated for use in SCI, but no measure was condition-specific to NBD. Eight measures were classified as subjective tools; two had an established reliability and validity for SCI while six had some psychometric evidence for use in the SCI population. Five subjective measures (NBD score, Burwood QoL Questionnaire, Impediments to Community Integration [ICI] Scale, SCI-QoL Bowel Management Difficulties, and Survey of Neurogenic Bowel Characteristics) were developed specifically for SCI. The NBD score showed sensitivity to the influence of NBD on QoL in experimental trials. Conclusion: Thirteen tools assessed the influence of NBD on QoL in SCI. Although not developed specifically for SCI, the Health Utility Index (HUI-III) was the only tool identified that provided data on "QoL as utility" on the impact of NBD. The validated NBD score was the only condition-specific tool to assess QoL as "subjective well-being." Further validation of existing tools could help to inform practice and policy related to resource allocation for bowel care post SCI.